1998
DOI: 10.1046/j.1365-2648.1998.00741.x
|View full text |Cite
|
Sign up to set email alerts
|

Caring, patient autonomy and the stigma of paternalism

Abstract: This paper utilizes data generated during a qualitative study in palliative and maternity care settings to guide discussion of the current discourse, which emphasizes patient autonomy and derides paternalism. Data are presented which illustrate that this ideology is established in nursing practice. Respect for patient autonomy is identified as an essential element of individualized, patient-centred and ethical care but conversely, it is suggested that overemphasis may confuse and suppress beneficent interventi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
55
0
6

Year Published

2004
2004
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 60 publications
(61 citation statements)
references
References 8 publications
0
55
0
6
Order By: Relevance
“…Results also revealed that patients' expression of more dominant (vs submissive) behaviours toward providers was positively related to both protein and energy intake measures. The beneficial impact of patients' agency echoes existing evidence for the adaptive role of one's autonomy on performance, well-being, medical compliance and learning (for a review see Ryan and Deci, 2000), as well as the current interest for more patient-centred and autonomy-supportive care (Woodward, 1998). Evidence also exists that one's autonomy can be fostered through social environments that are promoting choice, volition and freedom (Ryan and Deci, 2000).…”
Section: Discussionmentioning
confidence: 77%
“…Results also revealed that patients' expression of more dominant (vs submissive) behaviours toward providers was positively related to both protein and energy intake measures. The beneficial impact of patients' agency echoes existing evidence for the adaptive role of one's autonomy on performance, well-being, medical compliance and learning (for a review see Ryan and Deci, 2000), as well as the current interest for more patient-centred and autonomy-supportive care (Woodward, 1998). Evidence also exists that one's autonomy can be fostered through social environments that are promoting choice, volition and freedom (Ryan and Deci, 2000).…”
Section: Discussionmentioning
confidence: 77%
“…Whilst the medical and collaborative models of self-care and self-management are perceived by professionals as a legitimate and expected patient behaviour (Coates and Boore, 1995), there appears to be contrasting anxiety from the patient's perspective as to whether professionals see their self-care as legitimate (Stevenson et al, 2003). It should also be acknowledged that some patients may prefer to be managed rather than to self-manage (Woodward, 1998), and within the current policy climate of self-management not only being regarded as a right but also an obligation (Gilbert, 2005) there is always the potential for promotion of selfmanagement being coercive.…”
Section: Self-care and Self-management In Long-term Conditionsmentioning
confidence: 99%
“…Temptation to routinize care is very high when there are unrealistic work loads and time pressure (Woodward, 1998) whereas the nurse specialists were notable in working within clinics where there was sufficient time allowed to explore the patient perspective. Whilst the development of multidisciplinary teams is linked to the rhetoric of nursing autonomy, the reality is all too often that they are medically dominated (Cott, 1997).…”
Section: Implications For Nursing Practicementioning
confidence: 99%
“…Critics suggest that an overemphasis on autonomy stands to dehumanize health care, overlook caring and relation, and suppress moral agency (Dunbar, 2003;Woodward, 1998). Balancing the autonomy of the pregnant woman with the best interests of the fetus will require development and support of systems of care that are holistic, contextual, and long term.…”
Section: Discussionmentioning
confidence: 99%